Manichaeism in the Uyghur written monuments - Rustam, Kalikov (Turkic Studies Journal, 2022)
<!--StartFragment--> The article is devoted to the study of Manichaeism in Uyghur written monuments. Manichaeism is a religious belief that emerged in the Middle East in the 3rd century AD. Manichaeism contained Zoroastrian, Christian, Judaic, Mithraic and Buddhist elements. However, it is a holistic, complex religious system based on the dualistic philosophy of the struggle between good and evil, darkness and light, bright and dark. After the demise of the Old Turkic Khaganates, the Uyghur Begyu Khagan made Manichaeism the state religion of the Uyghur Khaganate. One of the reasons for the adoption of Manichaeism by the Uyghurs was the Begyu Khagan’s desire to establish relations with the Sogdians, the missionaries of Manichaeism, who were trying to spread it in East Turkestan, China and Mongolia. The spread of Manichaeism among the ancient Uyghurs is attested by Chinese and Arabic sources, but especially by several Uyghur monuments. Among these monuments is the Karabalgasun inscription, found by N.M. Yadrintsev in 1889 during an expedition to Mongolia, Ordu-Balyk (Karabalgasun). The author of the article analyzes the content of the Karabalgasun inscription and other Uyghur texts, explores the essence of the ideas of Manichaeism and reveals its origin, spread and close connection with Buddhism. <!--EndFragment-->